Critical Evaluation of Indian Historians’ Analysis of Buddhism - Katulkar, Ratnesh (Journal of International Buddhist Studies, 2016)
Buddhism is most prominent topic in the study ancient Indian history. The reason for its presence and visibility in Indian History owes to its presence on a wide time scale traverse during 6th century BC to 11th century AD. There are many special and unique features of the Buddhism reshaped not only Indian culture and society but it also played an eminent role in spreading its teachings to the world where it is still shining as a prominent religion. However, in its own birth land, the Buddhism was not able to preserve and save itself. Indian historians shared their diverse opinion on this subject but the most strange and weird observation in their writings is that they are all seems to be biased against the Buddhism. The eminent historians, for instance DN Jha opines, Buddhism as status quo movement which has followed the caste and untouchability in the same manner as that of Hinduism. Romila Thapar, claimed the great Buddhist monarch Ashoka as non-Buddhist and the concept of Dhamma as a continuation of ancient Hindu thoughts rather Buddhism. RC Majumdar says that the Dhamma was not policy of heretic but a system of beliefs created out of different religious faith. Irfan Habib went a step ahead by declaring that the Buddhist concept of Karma led to creations of caste and propagation of untouchability in India. So is the view of prominent author and ex-Buddhist monk Rahul Sankrityayan- who later turned towards Marxism. Ramvilas Sharma one of the famous leading fgure even claimed that there is hardly any scientifc teaching in Buddhism and whatever little logical things found available in it is the result and impact of Upanishads (on it). The overall common belief in Indian history is that the Buddhist teaching of non-violence and peace resulted in making Indians meek and weak which resulted in to her political slavery for centuries. A few scholars also claimed the Buddha to be anti-women and pro-establishment. Moreover, none of the historian fnds Ashokan regime-which was a well known to be welfare state-was seldom referred as a golden age of ancient India. But they did not hesitate to glorify the Gupta era as golden age which was in fact one of the darkest phases of Indian culture as it is the time when there was downfall of Buddhism and evil customs like Sati system, caste rigidness, and slavery were coming into society.